Range Automatic Adjusted Current Transformer Primary Winning - et.al, Amirov Sultan Fayzullayevich (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article discusses the issue of introducing a correction factor for protection and control devices, as the value of the secondary current in a certain range of the auto-adjustable current transformer does not correspond to the value of the secondary current in another range determined by the difference of magnetic driving forces generated by the components of the primary current. Alternatively, an algorithm has been developed to account for the measurement error in this condition in an automatic system that controls the operating mode of the current transformer. It was also found that the output data should be transmitted taking into account the correction factor in order to ensure the proper operation of the protection and measuring devices when the current transformer is switched to another measuring range in the measuring range.